MODERN RUSSIAN LITERATURE - Umirova Dilfuza Suyunovna; Khairullaeva Zarinabonu Khasanovna; Karimov Islom Odilbekovich (Journals Park Publishing, 2023)
First of all, literature is a collection of works based on the inner experiences of writers and, of course, about life events. Society finds in literature its real life, elevated to an ideal, brought to consciousness. ... Literature ... must be faithful to the people, must passionately and zealously stand up for its progress, prosperity and happiness.
Keywords: Modern Russian literature, styles, genre , works , writer, Society, experiences, events, Russia, book, era, process.